Effects of Adjuvant Administration of Macromolecules and Total Calories through Aggressive Parenteral Nutrition in Improvement of Neovascularisation of Infants with Retinopathy of Prematurity: A Literature Review - Tanto, Stefany; Octavius, Gilbert Sterling; Edgina, Alvita Suci (SCRIPTA SCORE Scientific Medical Journal, 2022)
Introduction: Retinopathy of Prematurity (ROP) is almost exclusively in premature infants. With advanced care and technology, the prevalence of retinopathy of prematurity in babies is increasing, which means the incidence of preventable blindness in ROP is increasing. Objectives: Â To evaluate the effects of protein, glucose, lipids, and total calories from Aggressive Parenteral Nutrition (APN) in improving neovascularisation of ROP in premature infants. Methods: We searched PubMed, Ophthalmology Advance, Scientific Reports, and Science Direct using the terms "Retinopathy of Prematurity", "Aggressive Parenteral Nutrition", "Prevalence of Retinopathy of Prematurity in Indonesia", "Protein", "Lipid", "Carbohydrate", "Glucose", "Total Calories", "Neovascularization", and "Prematurity" in various combinations. Results: We found three pieces of literature stating a positive association between APN and improvement of ROP, while one literature states that there is no significant change of prevalence of ROP by administering APN. Keywords: Aggressive Parenteral Nutrition, glucose, lipid, protein, Retinopathy of Prematurity Â  Pendahuluan: Retinopathy of Prematurity (ROP) adalah penyakit yang hampir secara eksklusif terjadi pada bayi prematur. Dengan perawatan dan teknologi yang canggih, prevalensi retinopati pada bayi prematur meningkat dan ini berarti kejadian kebutaan yang dapat dicegah pada ROP meningkat. Tujuan: Untuk mengevaluasi efek protein, glukosa, lipid, dan kalori total dari Nutrisi Parenteral Agresif (APN) dalam meningkatkan neovaskularisasi ROP pada bayi prematur. Metode: Kami mencari PubMed, Ophthalmology Advance, Scientific Reports dan Science Direct menggunakan istilah â€œRetinopathy of Prematurityâ€, â€œAggressive Parenteral Nutritionâ€, â€œPrevalence of Retinopathy of Prematurity in Indonesiaâ€, â€œProteinâ€, â€œLipidâ€, â€œCarbohydrateâ€ , "Glukosa", "Kalori Total", "Neovaskularisasi", dan "Prematuritas" dalam berbagai kombinasi. Hasil: Ditemukan tiga literatur yang menyatakan terdapat hubungan positif antara APN dengan peningkatan ROP sedangkan satu literatur menyatakan tidak ada perubahan signifikan prevalensi ROP dengan pemberian APN. Kata Kunci: Nutrisi Parenteral Agresif, glukosa, lipid, protein, Retinopati Prematuritas